Cranioplasty with autograft and bone grafting material: a clinical case study - A. A. Ofitserov; N. V. Borovkova; A. E. Talypov; M. S. Makarov; G. P. Titova; N. E. Kudryashova; O. V. Leshchinskaya; R. Sh. Muslimov; I. N. Ponomarev (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье)
A clinical study of the effectiveness of delayed cranioplasty with an autologous bone flap using allogenic bone grafting material was performed. The autograft was preserved, saturated with human collagen type 1, lyophilized and sterilized. Bone-plastic material was used to fill diastases. The patient was followed up in the postoperative period for 24 months. No clinical complications were registered. Radiological and radioisotope analysis showed normal fixation of the autograft after 6, 12 and 24 months. Biopsy analysis after 12 months showed the presence of regenerative processes in the absence of inflammation. The clinical result was assessed as successful.